Difference between revisions of "Math 22 Implicit Differentiation"
Jump to navigation
Jump to search
(6 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
==Implicit Differentiation== | ==Implicit Differentiation== | ||
− | Consider the equation <math>x^2y=5</math>. To find <math>\frac{dy}{dx}</math>, we can rewrite the equation as <math>y=\frac{5}{x^2}</math>, then differentiate as usual. ie: <math>y=\frac{5}{x^2}=5x^{-2}</math>, so <math>\frac{dy}{dx}=-10x^{-3}</math>. This is called explicit differentiation. However, sometimes, it is difficult to express <math>y</math> as a function of <math>x</math> explicitly. For example: <math>y^2-2x+4xy=5</math> | + | Consider the equation <math>x^2y=5</math>. To find <math>\frac{dy}{dx}</math>, we can rewrite the equation as <math>y=\frac{5}{x^2}</math>, then differentiate as usual. ie: <math>y=\frac{5}{x^2}=5x^{-2}</math>, so <math>\frac{dy}{dx}=-10x^{-3}</math>. This is called explicit differentiation. |
+ | |||
+ | However, sometimes, it is difficult to express <math>y</math> as a function of <math>x</math> explicitly. For example: <math>y^2-2x+4xy=5</math> | ||
Therefore, we can use the procedure called '''implicit differentiation''' | Therefore, we can use the procedure called '''implicit differentiation''' | ||
+ | |||
+ | ==Guidelines for Implicit Differentiation== | ||
+ | Consider an equation involving <math>x</math> and <math>y</math> in which <math>y</math> is a differentiable function of <math>x</math>. You can use the steps below to find <math>\frac{dy}{dx}</math>. | ||
+ | 1. Differentiate both sides of the equation with respect to <math>x</math>. | ||
+ | 2. Collect all terms involving <math>\frac{dy}{dx}</math> on the left side of the equation and move all other terms to the right side of the equation | ||
+ | 3. Factor <math>\frac{dy}{dx}</math> out of the left side of the equation. | ||
+ | 4. Solve for <math>\frac{dy}{dx}</math> by dividing both sides of the equation by the left-hand factor that does not contain <math>\frac{dy}{dx}</math>. | ||
+ | |||
+ | |||
+ | '''Example''': Find <math>\frac{dy}{dx}</math> of | ||
+ | |||
+ | '''1)''' <math>y^3=5x^3+8x</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>\frac{d}{dx}[y^3]=\frac{d}{dx}[5x^3+8x]</math> | ||
+ | |- | ||
+ | |<math>=3y^2\frac{dy}{dx}=\frac{d}{dx}[5x^3]+\frac{d}{dx}[8x]</math> | ||
+ | |- | ||
+ | |<math>=3y^2\frac{dy}{dx}=15x^2+8</math> | ||
+ | |- | ||
+ | |<math>=\frac{dy}{dx}=\frac{15x^2+8}{3y^2}</math> | ||
+ | |} | ||
+ | |||
+ | '''2)''' <math>x^2y+2xy+7=6x</math> | ||
+ | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Solution: | ||
+ | |- | ||
+ | |<math>\frac{d}{dx}[x^2y+2xy+7]=\frac{d}{dx}[6x]</math> | ||
+ | |- | ||
+ | |<math>=\frac{d}{dx}[x^2y]+\frac{d}{dx}[2xy]+\frac{d}{dx}[7]=6</math> | ||
+ | |- | ||
+ | |<math>=[2xy+x^2\frac{dy}{dx}]+[2y+2x\frac{dy}{dx}]+0=6</math> | ||
+ | |- | ||
+ | |<math>=x^2\frac{dy}{dx}+2x\frac{dy}{dx}=6-2xy-2y</math> | ||
+ | |- | ||
+ | |<math>=(x^2+2x)\frac{dy}{dx}=6-2xy-2y</math> | ||
+ | |- | ||
+ | |<math>=\frac{dy}{dx}=\frac{6-2xy-2y}{x^2+2x}</math> | ||
+ | |} | ||
− | |||
[[Math_22| '''Return to Topics Page''']] | [[Math_22| '''Return to Topics Page''']] | ||
'''This page were made by [[Contributors|Tri Phan]]''' | '''This page were made by [[Contributors|Tri Phan]]''' |
Latest revision as of 06:28, 27 July 2020
Implicit Differentiation
Consider the equation . To find , we can rewrite the equation as , then differentiate as usual. ie: , so . This is called explicit differentiation.
However, sometimes, it is difficult to express as a function of explicitly. For example:
Therefore, we can use the procedure called implicit differentiation
Guidelines for Implicit Differentiation
Consider an equation involving and in which is a differentiable function of . You can use the steps below to find . 1. Differentiate both sides of the equation with respect to . 2. Collect all terms involving on the left side of the equation and move all other terms to the right side of the equation 3. Factor out of the left side of the equation. 4. Solve for by dividing both sides of the equation by the left-hand factor that does not contain .
Example: Find of
1)
Solution: |
---|
2)
Solution: |
---|
This page were made by Tri Phan